2005
DOI: 10.1016/s0140-6736(05)17983-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of timing and method of enteral tube feeding for dysphagic stroke patients (FOOD): a multicentre randomised controlled trial

Abstract: SummaryBackground Undernutrition is common in patients admitted with stroke. We aimed to establish whether the timing and route of enteral tube feeding after stroke affected patients' outcomes at 6 months. MethodsThe FOOD trials consist of three pragmatic multicentre randomised controlled trials, two of which included dysphagic stroke patients. In one trial, patients enrolled within 7 days of admission were randomly allocated to early enteral tube feeding or no tube feeding for more than 7 days (early versus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 333 publications
(77 citation statements)
references
References 17 publications
1
76
0
Order By: Relevance
“…Although PEG represents a safer and more effective intervention to manage long-term dysphagia [27], the efficacy of its use in the acute phase of stroke recovery (<3 weeks) is disputable [28]. Further research is needed to assess the clinically effective timing of PEG placements to support functional recovery of activity participation (including oral nutrition and hydration) among patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Although PEG represents a safer and more effective intervention to manage long-term dysphagia [27], the efficacy of its use in the acute phase of stroke recovery (<3 weeks) is disputable [28]. Further research is needed to assess the clinically effective timing of PEG placements to support functional recovery of activity participation (including oral nutrition and hydration) among patients with acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Mild complications during insertion of a PEG may occur in 13–43% of patients, severe complications in 0.4–8.4%, the mortality reaching 0–2% where the type of disease, age, other risk factors all seem to influence outcome [260]. In patients who required tube feeding within the first 2 or 3 weeks of stroke, fatality and poor outcome were significantly higher for those who were fed via PEG than via a nasogastric tube (class I evidence [265]). After 4 weeks, however, nutrition via a PEG proved to be more effective compared to a nasogastric tube, but was associated with more adverse effects (class I evidence [266]).…”
Section: Dysphagiamentioning
confidence: 99%
“…Trials that enrolled critically ill patients demonstrated several benefits associated with enteral nutrition including improvements in nitrogen balance, splanchnic blood flow, gastrointestinal mucosal barrier function, mortality among mechanically ventilated patients and length of hospital stay [2, 3, 5, 6]. Evidence is less clear in patients suffering with an acute neurovascular event; protein-energy malnutrition during the first week after an acute stroke increased the risk of death or Barthel index ≤50 on the 30th day of follow-up 3.5-fold, whereas, the FOOD study, although suggesting a modest absolute risk reduction in mortality and poor functional outcome, was not statistically significant (1.2 %, −4.2 to 6.6, p  = 0.7) [7, 8]. …”
Section: Introductionmentioning
confidence: 99%